Attitudes of the general public towards the disclosure of individual research results and incidental findings from biobank genomic research in Australia. Issue 12 (December 2015) - Fleming, J.; Critchley, C.; Otlowski, M.; Stewart, C.; Kerridge, I.
Abstract: Background: Over the past decade, managing the disclosure of findings of genomic research has been the subject of extensive scientific, ethical and legal commentary and is a major challenge for biobanks. Aims: To examine views of the general Australian public about the disclosure of individual research results (IRR) and incidental findings (IF) from biobank genomic research. Methods: A national computer assisted telephone interview was conducted amongst a representative sample of ( n = 800) adult residents across each Australian State and Territory. Results: The majority of the Australian general public would be interested in receiving IRR and IF if they allowed their blood/tissue to be used in research; 94.4% ( n = 800) reported that they would like to receive 'specific information obtained from your sample that may be important to your health or treatment', and 83.4% their 'potential genetic risk of an inherited disease'. Although fewer desired to receive 'any IF that were not directly related to your (potential) diagnosed condition' (70.0%), most would still like to receive IF. A latent class analysis on the desire to receive (or not) all types of results revealed differences in preferences in the information they wished to receive. Conclusion: The majority of Australians desire to receive most information arising from research involving their tissue, including IRR and IF. Differences in the extent and type of information they desire to receive are noted. Biobanks must establish strategies to identify information needs of donors, assess research data and communicate with donors and donor families. Processes need to take account of differences in donor preferences and in the clinical or research context(s).